2021
DOI: 10.3389/fnagi.2020.625642
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Thickness Changes Over Time in a Murine AD Model APPNL-F/NL-F

Abstract: Background: Alzheimer's disease (AD) may present retinal changes before brain pathology, suggesting the retina as an accessible biomarker of AD. The present work is a diachronic study using spectral domain optical coherence tomography (SD-OCT) to determine the total retinal thickness and retinal nerve fiber layer (RNFL) thickness in an APPNL−F/NL−F mouse model of AD at 6, 9, 12, 15, 17, and 20 months old compared to wild type (WT) animals.Methods: Total retinal thickness and RNFL thickness were determined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
3
17
0
Order By: Relevance
“…However, in our work, no statistically significant brain changes were observed between participants with FH+ ApoE ɛ4+ and FH− ApoE ɛ4−. This result is supported by previous studies that showed that retinal changes appear earlier than brain changes [ 13 , 37 39 ]. Also, these retinal alterations, which could occur through retrograde transneuronal neurodegeneration [ 40 ], may be associated with atrophic brain changes already present before the appearance of clinical cognitive symptoms [ 17 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, in our work, no statistically significant brain changes were observed between participants with FH+ ApoE ɛ4+ and FH− ApoE ɛ4−. This result is supported by previous studies that showed that retinal changes appear earlier than brain changes [ 13 , 37 39 ]. Also, these retinal alterations, which could occur through retrograde transneuronal neurodegeneration [ 40 ], may be associated with atrophic brain changes already present before the appearance of clinical cognitive symptoms [ 17 , 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…At all ages studied, we found that the retina of 3×Tg-AD mice was thinner than that of age-matched WT mice. This is consistent with findings reported in the literature for animal models of AD (Chiquita et al, 2019a;Salobrar-García et al, 2021) and human patients (Marziani et al, 2013).…”
Section: Ad-induced Retinal Thickness Changessupporting
confidence: 93%
“…Mouse models have been important in multiple areas of research and have improved our understanding of disease pathophysiology. Based on OCT imaging, retinal changes induced by neurodegenerative diseases have been found, including changes in retinal layer thickness (Cunha et al, 2016 ; Song et al, 2020 ; Salobrar-García et al, 2021 ). Recently, we have also shown that retinal texture biomarkers can help discriminate between age-matched healthy controls and animal models of Alzheimer's disease (AD) in the early stages (Nunes et al, 2019 ; Ferreira et al, 2020 , 2022 ; Guimarães et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the possible alterations found in both the retina and choroid of subjects at high genetic risk of developing AD, who are also part of this study, and which we have reported in a previous work [ 21 , 30 ]. We have also demonstrated these alterations in the retina of a murine model of preclinical AD [ 37 ]. All these findings support the idea that the changes produced by AD may appear early in the retina, even before the onset of brain alterations [ 38 ].…”
Section: Discussionmentioning
confidence: 99%